PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 32 LUBUKLINGGAU - Enjeli, Vina; Pandra, Viktor; Putri, Widia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine whether the mathematics learning outcomes of fifth grade students at SD Negeri 32 Lubuklinggau significantly achieved the KKTP after the implementation of the Numbered Head Together (NHT) learning model. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 19 fifth grade students. Data were collected using a learning achievement test. The results showed that the mean pretest score increased from 38.58 to 75.79 in the posttest. The hypothesis testing indicated that the obtained tcount 3.92364 > ttable 1.73406 at a significance level of 0.05. Therefore, it can be concluded that the mathematics learning outcomes of fifth grade students at SD Negeri 32 Lubuklinggau after the implementation of the Numbered Head Together (NHT) learning model significantly achieved the KKTP.